PENGARUH RETURN ON ASSET (ROA), CURRENT RATIO (CR) DAN UKURAN PERUSAHAAN TERHADAP PRICE TO BOOK VALUE (PBV) PADA PT. ASTRA OTOPARTS, Tbk. - Maryana; Nurhayati (IAIN Lhokseumawe, 2022)
The purpose of this study was to determine the effect of Return On Assets (ROI), Current Ratio (CR) and Firm Size on Price To Book Value partially and simultaneously at PT. Otoparts, Tbk. Data collection techniques are documentation and literature study. The research population for 16 years starting from listing on the Indonesia Stock Exchange in 1997-2019. Then a sample of 10 years from 2011-2020 with purposive sampling technique. The data analysis technique used statistical analysis in the form of classical assumption test, multiple linear regression analysis of the coefficient of determination, t test and f test. The results showed that Return on Assets (ROA) had a partial and significant effect on Price To Book Value, Current Ratio (CR) and Firm Size had no partial and significant effect on Price To Book Value and Return On Assets (ROI), Current Ratio (CR) and Firm Size have a simultaneous effect on Price To Book Value.